m5C RNA Methylation Primarily Affects the ErbB and PI3K–Akt Signaling Pathways in Gastrointestinal Cancer - Xiang, Shixin; Ma, Yongshun; Shen, Jing; Zhao, Yueshui; Wu, Xu; Li, Mingxing; Yang, Xiao; Kaboli, Parham Jabbarzadeh; Du, Fukuan; Ji, Huijiao; Zheng, Yuan; Li, Xiang; et al. (Frontiers in Molecular Biosciences, 2020)
5-Methylcytosine (m5C) is a kind of methylation modification that occurs in both DNA and RNA and is present in the highly abundant tRNA and rRNA. It has an important impact on various human diseases including cancer. The function of m5C is modulated by regulatory proteins, including methyltransferases (writers) and special binding proteins (readers). This study aims at comprehensive study of the m5C RNA methylation-related genes and the main pathways under m5C RNA methylation in gastrointestinal (GI) cancer. Our result showed that the expression of m5C writers and reader was mostly up-regulated in GI cancer. The NSUN2 gene has the highest proportion of mutations found in GI cancer. Importantly, in liver cancer, higher expression of almost all m5C regulators was significantly associated with lower patient survival rate. In addition, the expression level of m5C-related genes is significantly different at various pathological stages. Finally, we have found through bioinformatics analysis that m5C regulatory proteins are closely related to the ErbB/PI3K–Akt signaling pathway and GSK3B was an important target for m5C regulators. Besides, the compound termed streptozotocin may be a key candidate drug targeting on GSK3B for molecular targeted therapy in GI cancer.